Analysis of Corporate University Programs and Their Relevance to E-Government Implementation in Indonesia - Wijaya, I Made Aldy; Alle, Elkis; Sudarmono, Sudarmono (Institut Pemerintahan Dalam Negeri, 2024)
Today's digitalization era demands system transformation in all sectors of life, including the government and bureaucratic sectors. State officials’ competence needs to be improved in order to adjust to the digital government environment (e-government). Education and training are essential for coping with the dynamic environment and enhancing the competency management of Civil Servants (ASN), as mandated by Law Number 5 of 2014 concerning ASN. This necessity has led to the emergence of the Corporate University concept in education and training units. This research aims to assess the relevance of the Corporate University program in developing ASN competencies to meet the challenges of e-government in Indonesia. The research employs descriptive methods and qualitative approaches, with data sourced from literature reviews. Data collection is conducted through documentation methods, and problem analysis utilizes Miles & Huberman's data analysis techniques, which include data reduction, data presentation, and conclusion drawing. The findings indicate that the Corporate University program is pertinent to the implementation of e-government, particularly in capacity building for civil servants through integrative learning and e-learning-based training in government agencies. Corporate University can be an effective solution to the need for digitally literate civil servants capable of operating an integrated digital service system, especially within local government, which is the closest government unit to the community.